ANALISIS PENYEDIAAN RUANG TERBUKA HIJAU PRIVAT (STUDI KASUS DI PERUMNAS SITEBA KELURAHAN SURAU GADANG KECAMATAN NANGGALO) - Pinezia Fitri Arsalina; Ratna Wilis (JURNAL BUANA, 2020)
ABSTRACT This study aims to analyze: (1) The process of changing the area of ​​private green open spaces in Siteba Perumnas (2) Provision of private green open space in Siteba Perumnas. This type of research is a descriptive quantitative. The research population was 810 people in Siteba National Housing Agency. Sampling using a random sampling technique with a proportion of 15% amount 118 respondents. Data collection techniques are observation and questionnaire distribution. The data analysis technique used is percentage. The results showed that: (1) Changes in the area of ​​Private Green Open Space as many as 98 respondents experienced changes in the area of ​​Private yards (RTH Private) once. Years of change in the area of ​​Private Green Open Space as many as 63 homes experienced changes in the area of ​​Private Green Open Space in the 1900s. The area of ​​Private Green Open Space starts from 4 m² to 20 m². Factors causing changes in the area of ​​the house yard (Private Green Open Space) in Perumnas Siteba flooding as much as 47.45% followed by a change in yard to a built area of 36.44% and small house plots of 16.10%. (2) The area of ​​private green open space in Siteba Perumnas was classified as low, the area of ​​Private Green Open Space in Situmn Perumnas was 187.32 m² or only 0.09% of the Siteba Perumnas area, availability of 1 protective tree 27.11%, and the availability of plants ≤ 7-10 as much as 46.61%. Keywords: Process Changes in Private Green Open Space, Provision of Private Green Open Space